A concise history of Italy - Duggan, Christopher (Cambridge concise histories, 2014)
Since its formation in 1861, Italy has struggled to develop an effective political system and a secure sense of national identity. This new edition of Christopher Duggan's acclaimed introduction charts the country's history from the fall of the Roman Empire in the west to the present day and surveys the difficulties Italy has faced during the last two centuries in forging a nation state. Duggan successfully weaves together political, economic, social and cultural history, and stresses the alternation between materialist and idealist programmes for forging a nation state. This second edition has been thoroughly revised and updated to offer increased coverage of nineteenth- and twentieth-century Italy, as well as a new section devoted to Italy in the twenty-first century. With a new, extensive bibliographical essay and a detailed chronology, this is the ideal resource for those seeking an authoritative and comprehensive introduction to Italian history